The effect of organic fertilizers on the spelt yield and the yield of its components - Pospišil, Ana; Pospišil, Milan, agronom (2021)
The aim of this study was to determine the effect of fertilization with organic fertilizers Fertil Supernova and Ilsamin N90 on the yield and yield components of three spelt varieties. The study was conducted on an anthropogenized eutric cambisol at the experimental site of the Faculty of Agriculture in Zagreb during 2015/16, 2016/17, and 2017/18, respectively. The study included three varieties of spelt, Nirvana, Ostro, and Bc Vigor, as well as a topdressing with organic fertilizers and a control (without topdressing). The first topdressing at the beginning of spring vegetation consisted of the application of organic fertilizer Fertil Supernova in the amount of 300 kg ha-1, while the second topdressing at the end of tillering consisted of a foliar application of Ilsamin N90 in the amount of 3 l ha-1. The spelt yield and its yield components were significantly influenced by weather conditions, primarily by the amount and distribution of precipitation. The studied spelt varieties did not significantly differ in the grain yield. In all three research years, the variety Nirvana has achieved the significantly largest number of ears per m2. Topdressing with organic fertilizers had a positive impact on the yield of the hulled spelt grain only in the dry year of 2016/17. Topdressing with organic fertilizers did not have a significant impact on the yield components.
Cilj istraživanja bio je utvrditi utjecaj prihrane organskim gnojivima Fertil Supernova i Ilsamin N90 na prinos i komponente prinosa triju sorata pira. Istraživanja su provedena na antropogeniziranome eutrično smeđem tlu na pokušalištu Agronomskoga fakulteta u Zagrebu tijekom 2015./16., 2016./17. i 2017./18. godine. U istraživanju su bile tri sorte pira: Nirvana, Ostro i Bc Vigor te prihrana organskim gnojivima i kontrola (bez prihrane). U prvoj prihrani na početku proljetne vegetacije primijenjeno je organsko gnojivo Fertil Supernova u količini od 300 kg ha-1, a u drugoj prihrani na kraju busanja folijarno je primijenjen Ilsamin N90 u dozi od 3 l ha-1. Na prinos i komponente prinosa pira značajno su utjecale vremenske prilike, prvenstveno količina i raspored oborina. Istraživane sorte nisu se značajno razlikovale u prinosu zrna. U sve tri godine istraživanja sorta Nirvana ostvarila je značajno najveći broj klasova po m2. Prihrana organskim gnojivima imala je pozitivan utjecaj na prinos neoljuštenoga zrna pira samo u sušnoj 2016./17. godini. Prihrana organskim gnojivima nije imala značajan utjecaj na komponente prinosa.
Bibliografija: 38 jed.
Summary ; Sažetak.
Keywords: Pir -- Prihrana -- Organska gnojiva -- Prinos -- Vremenske prilike